Kemampuan Kepala Madrasah dalam Mengembangkan Mutu Pendidikan di Diniyah Takmiliyah Awaliyah (DTA) Nurul Huda Desa Napal Sisik - Nurhafizi Ade Putra; Lily Hidayati; Reza Amanda (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2025)
This study aims to analyze the capabilities of the head of the madrasah in developing the quality of education at Diniyah Takmiliyah Awaliyah (DTA) Nurul Huda, Napal Sisik Village. The head of the madrasah plays a strategic role in enhancing educational quality through effective management, motivating teachers, and fostering creativity in the learning process. However, this study also identifies various challenges faced, such as a lack of qualified human resources, limited funding, and insufficient community support. By employing a qualitative approach, this research is expected to provide constructive recommendations for the improvement and development of the educational system at DTA, thereby creating a generation that is both intelligent and has strong character.